Influence of ethanol in spark ignition engine fuel consumption - Mohamad Waspi, Kassim Krismaran (2009)
Ethanol fuel is known as Gasohol blend, where there is E5, E85, E100 and etcetera. The figure shows percent of ethanol blend in gasoline. Main function of using gasohol is as alternative fuel. This blend can reduce reliability on gasoline. Using gasohol as fuel will affect engine performance, fuel consumption and emission. Ethanol in gasohol increases the octane number of the fuel, higher octane number fuel allow higher compression ratio in engine. For normal naturally-aspirated engine the common compression ratio is 10:1, but gasohol allow compression ratio up to 15:1. Higher compression ratio leads to better combustion and emissions. Experimentally, gasohol will cause increase in fuel consumptions but reduce in engine power and torque. For this project the engine used is Mitsubishi 4G92, four cylinder, water cooled, four-stroke, and 1.6L. The engine designed virtually in GT-Power software and all engine parameters remain constant. By using GT-Power simulation, brake fuel consumption of naturallyaspirated engine is tested using gasoline and gasohol as fuels. The fuel consumption of the engine was tested different rpm for both gasoline and gasohol. The result of the experiment is important to improve engine fuel consumptions which using gasohol as fuel and give advantages to gasohol engine designer to build reliable engine.